Neuromuscular efficiency of the quadriceps in women with and without patellofemoral pain - Paula, Julia Paixão De [UNESP]; Navega, Marcelo Tavella [UNESP]; Spinoso, Deborah Hebling [UNESP] (Universidade de São Paulo, 2023)
Patellofemoral pain (PFP) may contribute to less activation of the quadriceps muscle, favoring joint overload and pain. Neuromuscular efficiency (NME) is a variable that evaluates the relationship between the amount of neural stimuli and the ability to generate force of in a given muscle, with the most efficient being the one that produces greater muscle force, with less activation of muscle fibers. In this sense, this study aimed to evaluate the strength and NME of knee extensors in women with and without patellofemoral pain. A total of 24 adult women, recruited via a questionnaire, aged from 18 to 30 years, with and without patellofemoral pain, participated in this study. Anamnesis, anterior knee pain scale, and numerical visual scale were applied. Subsequently, the knee extensor strength, with a hand-held dynamometer, and the NME of vastus medialis (VM), vastus lateralis (VL), and rectus femoris (RF) were assessed. For statistical analysis, appropriate tests were adopted to compare variables between groups and correlate them. In all statistical tests, a α<0.05 was adopted. Results showed that women with PFP had 61% lower NME in the VM and 52% in the VL, compared to the group without pain. No significant difference was found for knee extensor strength between groups. We conclude that pain negatively influences VM and VL recruitment but does not change quadriceps ability to generate strength.

El dolor patelofemoral (DPF) puede producir una menor activación del músculo cuádriceps, lo que lleva a una mayor sobrecarga y dolor en esta articulación. La eficiencia neuromuscular (ENM) es una variable que evalúa la relación entre la cantidad de estímulos neurales y la capacidad de determinado músculo de generar fuerza, con más eficiencia para el que produce mayor fuerza muscular, con menor activación de las fibras musculares. Así el objetivo del estudio fue evaluar la fuerza y la ENM de los extensores de rodilla en mujeres con y sin dolor patelofemoral. En este estudio participaron 24 mujeres, con edades entre 18 y 30 años, con y sin dolor patelofemoral, que han sido reclutadas por medio de un cuestionario. Se aplicaron la anamnesis, la escala de dolor anterior de rodilla y la escala visual numérica. Posteriormente, se realizaron evaluaciones de la fuerza extensora de la rodilla con dinamómetro manual y de la ENM del vasto medial (VM), vasto lateral (VL) y recto femoral (RF). Para el análisis estadístico, se adoptaron pruebas apropiadas para comparar variables entre grupos y correlacionarlas. En todas las pruebas estadísticas, el nivel de significación fue de α<0,05. Los resultados mostraron que las mujeres con DPF tenían el 61% menor ENM en el VM y el 52% en el VL en comparación con el grupo sin dolor. No hubo diferencias significativas para la fuerza extensora de la rodilla entre los grupos. Se concluye que el dolor influye negativamente en el reclutamiento de VM y VL, pero no cambia la capacidad de generar fuerza del cuádriceps.
Eficiencia neuromuscular del cuádriceps en mujeres con y sin dolor patelofemoral
Keywords: Muscle Strength; Electromyography; Knee